Mobile Edge Computing: Review and Analysis - Kharbanda, Komal; Kaur, Kiranbir (International Journal of Computer Sciences and Engineering, 2019)
These days with intense use of mobile applications and cloud computing, mobile cloud computing has been acquainted. The cloud computing deals with high latency, limited flexibility, platform dependency. The mobile edge computing(MEC) combines cloud computing and wireless communication to overpower the obstacles of delay, scalability and mobility. MEC helps to bring the various resources and cloud computing services nearer and accessible anywhere by the user with the use of mobile edge clouds(MEC). In this paper we provide an extensive survey of mobile edge computing research, while highlighting the specific concerns in mobile cloud computing. We present a taxonomy based on the key issues in this area, and discuss the different approaches taken to tackle these issues.